The quality of liquid biostimulant formula of microbial-based during packaging and storage - Radiastuti, Nani; Susilowati, Dwi Ningsih; Rahayu, Rizkiyah Putri; Kosasih, Jajang; Tentrem, Titi (Biogenesis: Jurnal Ilmiah Biologi, 2024)
.